1994
DOI: 10.1111/j.1439-0388.1994.tb00461.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of maternal ability in Iberian pigs

Abstract: A practical measure of milk yield of the sow is the weight of the litter at three weeks of age when the piglet growth is entirely dependent on the milking ability of the dam. Genetic parameters of litter size at birth (LS) and litter weight at 21 days (LW21) were estimated using a DFREML procedure from records of 4883 litters (2,049 for LW21) of Iberian breed. Preliminary analysis showed negligible maternal genetic effects. The model for both traits included the fixed effects of farrowing period (86 levels), p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
12
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 12 publications
3
12
0
Order By: Relevance
“…Estimated genetic parameters of W4w, with a low heritability of direct effects, a much larger maternal heritability and a moderate genetic antagonism between direct and maternal effects, are consistent with early literature results (reviewed by Robison [35]). They are also similar to the results obtained at 3 weeks of age by Rodriguez et al [36] in Iberian pigs (with a lower antagonism between direct and maternal effects) and at 4 weeks of age by Maignel et al ([26] and unpublished results) in Large White and Landrace breeds. These results suggest that piglet preweaning growth is to a larger extent under the control of the environment provided by the dam than of the piglets' individual genes.…”
Section: Discussionsupporting
confidence: 80%
“…Estimated genetic parameters of W4w, with a low heritability of direct effects, a much larger maternal heritability and a moderate genetic antagonism between direct and maternal effects, are consistent with early literature results (reviewed by Robison [35]). They are also similar to the results obtained at 3 weeks of age by Rodriguez et al [36] in Iberian pigs (with a lower antagonism between direct and maternal effects) and at 4 weeks of age by Maignel et al ([26] and unpublished results) in Large White and Landrace breeds. These results suggest that piglet preweaning growth is to a larger extent under the control of the environment provided by the dam than of the piglets' individual genes.…”
Section: Discussionsupporting
confidence: 80%
“…In Iberian pigs, Rodríguez et al (1994) found that the litters and individual piglets heaviest at weaning are those born in the second parity and, thereafter, a negative effect of parity on piglet and litter weight is observed. More recently, Fernández et al (2005) from analyses fitting random regression models described a similar negative relationship between litter weight at weaning (maternal ability) and parity order.…”
Section: Discussionmentioning
confidence: 99%
“…According to the estimated parity effects on LW21, the best mothering ability of Torbiscal sows is achieved at parity 2 and it slightly decreases in the later parities, being similar the maternal aptitude of sows at the parities 1 and 5. Moreover, in this Iberian line the parity effect on individual piglet weight at 21 days is also maximum at parity 2 and decreases monotonically even after the parity 6 (Rodríguez et al, 1994).…”
Section: Analysis With Repeatability Animal Model (Rm)mentioning
confidence: 94%
“…An increase of litter size at birth up to fifth parity has been previously reported in Torbiscal and other Iberian pig strains by Pérez-Enciso and Gianola (1992) and Rodríguez et al (1994). Mothering ability measured by LW21 may be considered as a composite trait, combining litter size and average piglet weight at 21 days, which depend on the number of piglets born and the piglets preweaning survival and growth.…”
Section: Analysis With Repeatability Animal Model (Rm)mentioning
confidence: 99%
See 1 more Smart Citation